Natural radionuclide distribution and analysis of associated radiological concerns in rock samples from a rocky town (Dutsin-Ma) in the North-Western region of Nigeria - Emmanuel Joseph; Gonto Kamal; Oluwasesan M. Bello (African Scientific Reports, 2023)
Natural radionuclides in rock samples, especially 226Ra (Radon), 232Th (thorium), and 40K (potassium), are the primary source of exposure to radiation for employees and the public, and their detection is critical for radiation safety. The gamma (γ) radiation from natural radionuclides was quantified using the γ-ray spectrometry method in twenty rock samples obtained from Dutsin-Ma, a rocky town in Nigeria's north-western region. The data obtained were used to estimate the radiological parameters and the excess lifetime cancer risk (ELCR). The results obtained show that the minimum activity concentrations of 40K, 232Th, and 226Ra are respectively 36.7 Bq/kg, 25.99 Bq/kg, and 11.59 Bq/kg, with their maximum values being 73.23 Bq/kg, 92.81 Bq/kg and 100.93 Bq/kg respectively. The average activity of 40K, 232Th, and 226Ra in the rock samples were found to be 73.5781±3.38 Bq/kg, 40.7848±3.32 Bq/kg, and 33.6616±3.58 Bq/kg respectively, which were all below the World average values of (33, 45 and 420) Bq/kg respectively. The ELCR was found to be 0.185±0.01, while the average absorbed dose rate, as well as the mean annual effective dose rate, were calculated to be 43.13±2.7 nGy/h and 0.015±0.003 mSv/y respectively. The outcomes for internal hazard, external hazard, annual absorbed and effective dose equivalent (ABEDE), alpha and gamma index values were below the maximum values allowed limits of 1 mSv/y for ABEDE and 1 for representative alpha & gamma index values, internal and external hazards as recommended by the International Commission on Radiological Protection (ICRP). This study shows that the radiation contamination of rock particles in Dutsin-Ma LGA does not pose much significant risk.